2007
DOI: 10.1111/j.1467-7652.2007.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant antibody 2G12 produced in maize endosperm efficiently neutralizes HIV‐1 and contains predominantly single‐GlcNAc N‐glycans

Abstract: SummaryAntibody 2G12 is one of a small number of human immunoglobulin G (IgG) monoclonal antibodies exhibiting potent and broad human immunodeficiency virus-1 (HIV-1)-neutralizing activity in vitro , and the ability to prevent HIV-1 infection in animal models.It could be used to treat or prevent HIV-1 infection in humans, although to be effective it would need to be produced on a very large scale. We have therefore expressed this antibody in maize, which could facilitate inexpensive, large-scale production. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
134
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(145 citation statements)
references
References 66 publications
(82 reference statements)
10
134
1
Order By: Relevance
“…In consequence, the development phase for recombinant mAb production is accelerated. Nevertheless, form the pionner work of Hiatt et al [13] to the most recent production of anti-HIV prophylactic IgG in corn [21,22], the lengthy process of establishing a homozygous transgenic plant line with stable and homogeneous IgG production has been the Achilles' heel of plant-made antibodies.…”
Section: Full Size Antibodiesmentioning
confidence: 99%
“…In consequence, the development phase for recombinant mAb production is accelerated. Nevertheless, form the pionner work of Hiatt et al [13] to the most recent production of anti-HIV prophylactic IgG in corn [21,22], the lengthy process of establishing a homozygous transgenic plant line with stable and homogeneous IgG production has been the Achilles' heel of plant-made antibodies.…”
Section: Full Size Antibodiesmentioning
confidence: 99%
“…Antibody concentrations were measured by surface plasmon resonance as described previously using a BIACORE 2000 (Biacore; GE Healthcare; Rademacher et al, 2008). 2G12 accumulation was measured from triplicate leaf extracts representing infiltrated tissue from six plants.…”
Section: G12 Measurementsmentioning
confidence: 99%
“…not cleave off a single GlcNAc); and 3) it is difficult to retain short glycan structures in released glycan analysis. It also has been observed that recombinant proteins expressed in plants can have glycans trimmed to a single sugar residue (32,33). The sample preparation for this study did not make a specific attempt to solubilize transmembrane proteins, so the results here may be biased toward more soluble proteins, with many Golgi-resident proteins identified.…”
Section: Discussionmentioning
confidence: 75%